2018
DOI: 10.1371/journal.pone.0196197
|View full text |Cite
|
Sign up to set email alerts
|

Performance on the APACHE II, SAPS II, SOFA and the OHCA score of post-cardiac arrest patients treated with therapeutic hypothermia

Abstract: ObjectiveThis study assessed the ability of the Acute Physiologic and Chronic Health Evaluation (APACHE) II score, Simplified Acute Physiology Score (SAPS) II, Sequential Organ Failure Assessment (SOFA) score, and out-of-hospital cardiac arrest (OHCA) score to predict the outcome of OHCA patients who underwent therapeutic hypothermia (TH).MethodsThis study included OHCA patients treated with TH between January 2010 and December 2013. The APACHE II score, SAPS II, and SOFA score were calculated at the time of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…Previous studies have shown an association of admission SOFA and EC-SOFA with 28-/30-day mortality in single-centre settings of OHCA patients [13, 24, 25]. Association with neurologic outcome has produced conflicting results [24, 25].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown an association of admission SOFA and EC-SOFA with 28-/30-day mortality in single-centre settings of OHCA patients [13, 24, 25]. Association with neurologic outcome has produced conflicting results [24, 25].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, each prediction model has been compared with others, improved by adding new factors, or validated based on several other demographic features to overcome worldwide variations [1,[11][12][13]. However, there is still a shortage of external validation studies, and no…”
Section: Introductionmentioning
confidence: 99%
“…[ 26 , 27 ] APACHE II score is more likely to evaluate the severity of the disease, while SOFA score is more inclined to evaluate the organ injury of the patient Though the sensitivity of assessment ability varies between them, both are associated with severity or mortality for critically patients. [ 28 ] It may be more persuasive to use both scores together. Our results also showed that these 2 scores were associated with sepsis severity.…”
Section: Discussionmentioning
confidence: 99%
“…OF note, PCT was only molecule significantly correlated with both the APACHE II score ( r = 0.36) and SOFA score ( r = 0.50) as observed previously. [ 28 ] Additionally, plasma NGAL ( r = 0.31) was positively correlated with SOFA score. Quantitatively, PCT and NGAL concentrations were significantly higher in the sepsis shock group than in the sepsis group.…”
Section: Discussionmentioning
confidence: 99%